Acute and Chronic Hepatitis E Virus Infection in Human Immunodeficiency Virus‐Infected U.S. Women. Issue 3 (16th January 2016) - Kuniholm, Mark H.; Ong, Edgar; Hogema, Boris M.; Koppelman, Marco; Anastos, Kathryn; Peters, Marion G.; Seaberg, Eric C.; Chen, Yue; Nelson, Kenrad E.; Linnen, Jeffrey M.
Abstract : Exposure to hepatitis E virus (HEV) is common in the United States, but there are few data on prevalence of HEV/human immunodeficiency virus (HIV) coinfection in U.S. populations. We tested 2, 919 plasma samples collected from HIV‐infected (HIV + ) women and men enrolled in U.S. cohort studies for HEV viremia using a high‐throughput nucleic acid testing (NAT) platform. NAT + samples were confirmed by real‐time polymerase chain reaction. Samples were selected for testing primarily on the basis of biomarkers of liver disease and immune suppression. Prevalence of HEV viremia was 3 of 2, 606 and 0 of 313 in tested plasma samples collected from HIV + women and men, respectively. All HEV isolates were genotype 3a. Based on follow‐up testing of stored samples, 1 woman had chronic HEV infection for >4 years whereas 2 women had acute HEV detectable at only a single study visit. Conclusions: To our knowledge, this is the first reported case of chronic HEV infection in an HIV + U.S. individual. We also confirm that chronic HEV infection can persist despite a CD4 + count >200 cells/mm 3 . Overall, though, these data suggest that HEV infection is rare in the HIV + U.S. population. (Hepatology 2016;63:712–720)